Characterization of a novel capsaicin/heat ongoing pain model. (6th October 2017) - Price, R.C.; Gandhi, W.; Nadeau, C.; Tarnavskiy, R.; Qu, A.; Fahey, E.; Stone, L.; Schweinhardt, P.
Abstract: Background: Human experimental pain models provide an important translational link between pre‐clinical models and clinical pain. Using topical capsaicin and continuous heat application, the novel capsaicin/heat ongoing pain (CHOP) model induces long‐lasting experimental pain of which the perceived intensity can be individually adjusted. Methods: In the CHOP model, capsaicin or control cream is applied to a 10 × 10 cm skin area and a heating pad is applied over the area after cream removal. Two experiments in healthy participants were performed for model characterization. In Experiment 1, a constant temperature was applied for 60 min; in Experiment 2, temperature was adjusted to maintain a constant perceived intensity for 60 min. Results: Experiment 1: across participants, constant temperature induced initial habituation followed by an increase in sensation back to baseline. Cluster analysis revealed that half the participants sensitized to the constant temperature, while the other half did not. The degree of sensitization was related to the baseline pain unpleasantness, relative to pain intensity. Experiment 2: constant perceived intensity was achieved in the painful and a non‐painful control condition. The two conditions did not differ regarding possibly confounding variables, including blood pressure, heart rate, inflammation or physiological stress as measured by surrogate markers. Secondary allodynia and hyperalgesia were reported more following painful compared to control stimulation. Sensitizers as determined in Experiment 1 were also more pain sensitive in Experiment 2. Conclusion: The CHOP model reproduces some aspects of clinical pain, such as longer duration, sensitization, secondary allodynia and hyperalgesia. Significance: Here we demonstrate a novel pain model that can be applied for up to an hour without tissue damage. The CHOP model allows for investigation of primary and secondary hyperalgesia as well as top‐down influences on sensitization, thereby providing an experimental model that can be used to assess clinically‐oriented questions.